A Quo Vadis: Competency Resilience of Rural and Border Areas Healthcare Workers. Is It Sufficient? - Ningrum, Dwi Asih Kartika; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: This study analyzes the need for competency adjustments among healthcare workers in rural and border areas. The novelty of this research lies in exploring existing education and training curricula and identifying specific needs to enhance healthcare services in rural areas, focusing on improving resilience and retention skills among healthcare workers. Methods: This study employs a literature review to formulate an appropriate education and training curriculum. The primary focus is identifying specific needs to improve healthcare services in rural and border areas. Results: The study found significant health issues related to the high risk of disease transmission, lack of facilities, and low retention of healthcare workers in cross-border health facilities. The National Border Management Agency has identified 222 border-crossing subdistricts requiring strengthened healthcare services. Healthcare workers in rural and border areas face unique challenges requiring specialized knowledge and skills, including health resilience involving readiness to handle disease outbreaks or natural disasters and adaptation to limited conditions. Current health education may not be sufficient to prepare professionals for these challenges. Efforts through rural internships during pre-service education are considered inadequate unless aligned with a specific rural curriculum. The Contextual Learning Model emphasizes learning through real-world situations and is the theoretical framework for curriculum development. This curriculum aims to enhance the understanding and management of health issues in everyday contexts, promoting the principles of social accountability in higher health profession education. Conclusion: Adjusting the competencies of healthcare workers in rural and border areas is crucial to improving healthcare quality. Recommendations are provided to policymakers to develop training programs tailored to the specific needs of healthcare workers in these areas, supported by infrastructure development to facilitate access to education and training. The primary outcome expected is improved community access to and quality of healthcare services in these regions.